Internal Locus of Control dan Efek Computer Anxiety pada Kinerja Karyawan Keuangan - Juniariani, Ni Made Rai; Saputra, Komang Adi Kurniawan (Universitas Pendidikan Ganesha, 2020)
This study aims to analyze the influence of computer anxiety on financial employee performance and to analyze whether the internal locus of control moderate the influence of computer anxiety on financial employee performance. This research is expected to be able to give consideration to Lembaga Perkreditan Desa (LPD) to routinely provide training in both computer training and personality training to their employees so that their employees are capable of operating financial computer programs that are used and have good personalities and are able to provide maximum services to the public. The data used are primary data in the form of answers to questionnaires distributed to LPD employees in the Kota Denpasar. The analysis technique used to answer the research hypothesis is Moderated Regression Analysis (MRA). Hypothesis testing results show that computer anxiety has a negative effect on financial employee performance, and internal locus of control weakens the influence of computer anxiety on financial employee performance.Â